Analyzed Quality Question Type Multiple Choices Questions (MCQ) of Final Exam Even Semester on Biology Course Class XI SMA Negeri Se-Kecamatan IV Jurai Academic Year 2017/2018 - Nadya Khairiyah Syafti; Rahmawati Darussyamsu; Ganda Hijrah Selaras; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Researcher conducted a study with the aim to determine the quality of items in terms of analysis: 1) reliability, 2) the validity of the content and empirical, 3) distinguishing features, 4) level of difficulty, and 5) the function of detractors. This research is a descriptive study. Based on the results of data analysis, the result for the review of aspects: 1)reliability packet A and B, belong to the category high,2)the validity of the content packet A & B, not fulfilling all criteriaand then validity empirically package A, 57.5% are invalid matter and packet B,65% are invalid matte, 3) the level of difficulty package A, 27 questions (67,5%) good category and 13 questions (32,5%) not good category while package B, 27 questions (67,5%) good category and 13 questions (32,5%) not good category. 4) different power packet A, obtained with different power values, namely 35 questions (87,5%) including good categories and 5 questions (12,5) which do not belong to the good category while package B, 29 questions (72,5%) is included in category and 11 questions (27,5%) which do not belong to category, 5) function options packet A, for options that are not qualified is 37% and the quality is 63% and packet B,for options that are not qualified is 31% and the quality is 69%. It can be concluded that the end of the semester exam subjects biology grade XI of the school year 2017/2018 in the se-kecamatan IV Jurai not meet both criteria.